2020
DOI: 10.1002/wer.1296
|View full text |Cite
|
Sign up to set email alerts
|

Sensor‐mediated granular sludge reactor for nitrogen removal and reduced aeration demand using a dilute wastewater

Abstract: A sensor‐mediated strategy was applied to a laboratory‐scale granular sludge reactor (GSR) to demonstrate that energy‐efficient inorganic nitrogen removal is possible with a dilute mainstream wastewater. The GSR was fed a dilute wastewater designed to simulate an A‐stage mainstream anaerobic treatment process. DO, pH, and ammonia/nitrate sensors measured water quality as part of a real‐time control strategy that resulted in low‐energy nitrogen removal. At a low COD (0.2 kg m −3 day … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The reactor was operated to simulate treatment of an effluent from a mainstream anaerobic process. Synthetic influent (20 L) was prepared as described elsewhere (Bekele et al ., 2020) and in the Supporting Information. The synthetic influent was prepared approximately every 2 days using glassware that was autoclaved prior to influent preparation.…”
Section: Methodsmentioning
confidence: 99%
“…The reactor was operated to simulate treatment of an effluent from a mainstream anaerobic process. Synthetic influent (20 L) was prepared as described elsewhere (Bekele et al ., 2020) and in the Supporting Information. The synthetic influent was prepared approximately every 2 days using glassware that was autoclaved prior to influent preparation.…”
Section: Methodsmentioning
confidence: 99%
“…pH was controlled at a set point of 7.4 by sodium bicarbonate addition. Synthetic influent was meant to simulate mainstream anaerobic effluents and has been previously described , and contained 50 mg of NH 4 + -N/L, varying sulfide concentrations, and a target methane concentration at saturation.…”
Section: Methodsmentioning
confidence: 99%
“…Sulfide- and methane-rich wastewater would also result from anaerobic treatment processes because sulfate reducing bacteria convert the sulfate to sulfide, and there is residual dissolved methane in anaerobic effluents. For these reasons, there is ongoing research on harnessing sulfide or methane as an electron donor for denitrification (e.g., ). Several published studies have focused on one-stage nitrogen removal using either methane or sulfide as electron donors, , but to our knowledge, no studies have evaluated the application of both methane and sulfide for nitrogen removal in single-stage nitrogen removal reactors that support oxic and anoxic environments. ,, …”
Section: Introductionmentioning
confidence: 99%
“…It showed the great performance to control the pilot WWTP (Baeza, Gabriel, & Lafuente, 1999). A sensor-mediated (coupled with residual ammonia controls and DO set-point) approach is implemented on a granular sludge reactor to remove nutrients in wastewater and showed that maintaining stable aerobic granular sludge will help to improve the performance (Bekele, Delgado Vela, Bott, & Love, 2020). Control options using the TSS controller with a high ratio of food to microbes in the reactor in the BSM2 framework reduced the risk and effect of bulking sludge (Flores-Alsina et al, 2009).…”
Section: Introductionmentioning
confidence: 99%